2018
DOI: 10.3748/wjg.v24.i24.2628
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between uncut Roux-en-Y and Roux-en-Y reconstruction after distal gastrectomy for gastric cancer: A meta-analysis

Abstract: AIMTo compare uncut Roux-en-Y (U-RY) gastrojejunostomy with Roux-en-Y (RY) gastrojejunostomy after distal gastrectomy (DG) for gastric cancer.METHODSA literature search was conducted in Pubmed, Embase, Web of Science, Cochrane Library, Science Direct, Chinese National Knowledge Infrastructure, Wanfang, and China Science and Technology Journal Database to identify studies comparing U-RY with RY after DG for gastric cancer until the end of December 2017. Pooled odds ratio or weighted mean difference with 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
2
14
1
1
Order By: Relevance
“…Moreover, even if the postoperative complications of the Uncut Roux-Y group were similar to those of the Roux-Y group, Uncut Roux-Y anastomosis should still be the first choice due to its simplicity and costeffectiveness. Nevertheless, these data represent the results of six consecutive years at a specialized centre for gastric cancer surgery in a Chinese hospital, and at the very least, and these data support the previous studies in other centres that demonstrated the Uncut Roux-Y is an excellent method of anastomosis for distal gastrectomy, which is feasible as a laparoscopic surgery [23,24]. There are few limitations too, it is possible that the ligature was not effective and the closure failed at efferent loop of jejunum in Uncut Roux-Y patients.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, even if the postoperative complications of the Uncut Roux-Y group were similar to those of the Roux-Y group, Uncut Roux-Y anastomosis should still be the first choice due to its simplicity and costeffectiveness. Nevertheless, these data represent the results of six consecutive years at a specialized centre for gastric cancer surgery in a Chinese hospital, and at the very least, and these data support the previous studies in other centres that demonstrated the Uncut Roux-Y is an excellent method of anastomosis for distal gastrectomy, which is feasible as a laparoscopic surgery [23,24]. There are few limitations too, it is possible that the ligature was not effective and the closure failed at efferent loop of jejunum in Uncut Roux-Y patients.…”
Section: Discussionsupporting
confidence: 86%
“…Roux-en-Y anastomosis requires two anastomoses, and thus increases the number of intestinal stumps, which requires rather complicated steps. Also, like Billroth II anastomosis, Roux-en-Y anastomosis does not highly conform to the human physiology and anatomy [8,12]…”
Section: Discussionmentioning
confidence: 99%
“…Two reviewers (CPW and JG) independently assessed the methodological quality of all included studies by using the Newcastle–Ottawa scale (NOS). [10,11] scale with a maximum of nine stars was adopted for the evaluation of the selection, comparability, exposure, and outcome of each study. Studies with a NOS scores of >7 were considered high-quality works.…”
Section: Methodsmentioning
confidence: 99%